2021
DOI: 10.7860/jcdr/2021/49835.15185
|View full text |Cite
|
Sign up to set email alerts
|

Blood Gas Analysis among COVID-19 Patients: A Single Centre Retrospective Observational Study

Abstract: Introduction: The dominant respiratory feature of Coronavirus Disease 2019 (COVID-19) is arterial hypoxaemia, greatly exceeding abnormalities in pulmonary mechanics. Arterial Blood Gas (ABG) analysis helps to find out respiratory, metabolic acidosis and alkalosis. Aim: To evaluate the blood gas levels among critically ill COVID- 19 positive patients admitted in Intensive Care Unit (ICU). Materials and Methods: A retrospective, observational study was conducted in East Midnapore district of West Bengal, India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The prevalence of inappropriate responders is consistent with estimates of respiratory alkalosis in 28.7–55.4% from other studies that investigated blood gas analysis in hospitalized COVID-19 patients [( 5 ) (55.4%); ( 6 ) (28.7%); ( 7 ) (30.3%); ( 8 ) (40.4%)]. Wu et al ( 6 ) found higher inflammatory markers in respiratory alkalosis group, and other studies corroborate admission hypocapnia as a marker of severe disease ( 17 , 18 ).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The prevalence of inappropriate responders is consistent with estimates of respiratory alkalosis in 28.7–55.4% from other studies that investigated blood gas analysis in hospitalized COVID-19 patients [( 5 ) (55.4%); ( 6 ) (28.7%); ( 7 ) (30.3%); ( 8 ) (40.4%)]. Wu et al ( 6 ) found higher inflammatory markers in respiratory alkalosis group, and other studies corroborate admission hypocapnia as a marker of severe disease ( 17 , 18 ).…”
Section: Discussionsupporting
confidence: 88%
“…Of the total cohort, 38% (74/194), had a 6-week follow-up after hospital discharge, of which 34 (17.5%) were face-to-face consultations which allowed full clinical assessment. A new diagnosis of breathing pattern disorder (BPD) was made in 23.5% (8/34), with a BPAT score of 6 ( 5 7 ). None had a past medical history of respiratory, neurological or psychiatric disorder.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In clinical practice, the use of corticosteroids in the past, whether at home or in any other hospital environment, may also cause metabolic alkalosis by activating the mineralocorticoid system, but it cannot be connected directly to respiratory alkalosis [8]. In this study, 15 (5.6%) patients also presented with metabolic alkalosis.…”
Section: Discussionmentioning
confidence: 55%